O POVO DO ASHÈ: A IMPORTÂNCIA DAS RELIGIÕES DE MATRIZ AFRICANA PARA PRESERVAÇÃO DA BIODIVERSIDADE ECOLÓGICA, CULTURAL E SOCIOAMBIENTAL (Revista Paradigma, 2022)
The paper presents as proposal a stimulating and innovative alternative feasible for preservation and social and environmental protection. Considering the preservation of the socio-cultural aspects and ancestral practices of the religious communities of African territory or matrix, which by their own liturgy preserve and worship specific forces or manifestations of nature is above all to increase the volume of organized people with the aim of preserving the environment protecting the natural resources and guaranteeing sustainable development in the various communities throughout the country. Nevertheless, we seek to unveil the veil of prejudice that covers Brazilian socio-environmental inequality, as well as to present legal actions and legal measures to encourage the preservation and protection of the ecological, cultural and religious biodiversity of these communities. Through bibliographical and documentary research it is possible to aggregate data and information that allow from the deductive method to perceive the importance of the objective to be achieved, structuring in a structural way the necessary arguments to demonstrate the feasibility of protecting and preserving the ecological and environmental ensemble of the traditional communities, especially the ashè people. Therefore, it is possible to verify that the traditional communities of African matrix, play a fundamental role in the sustainable maintenance of the ecosystems. Thus, it is necessary to conclude about the importance of the terreiro peoples and the socio-environmental role they play in promoting preservation and environmental protection.